KARAKTERISTIK PERUSAHAAN YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN ITEM VOLUNTARY DALAM LAPORAN KEUANGAN PERUSAHAAN PUBLIK DI INDONESIA - Sabeni, Arifin (JURNAL AKUNTANSI DAN AUDITING, 2013)
This research is aimed a) to identify the level of voluntary disclosure by using Voluntary DisclosureIndex, and b) to analyze the firm’s characteristics that have significant impact on disclosure levelof each firm in certain industry. The Descriptive statistics and multiple regression analysis areused to examine these objectives, particularly for analyzing firm’s characteristic ( such as board ofdirectors composition, the number of audit committee’s member, firm’s size, leverage, profitability,firm’s operations, and the industry types) and their impact on the voluntary disclosure level. Theresults  by using descriptive statistics show that the mining industry have the highest voluntarydisclosure Index (VDI), followed by infra structure and transportation industry, then agricultureindustry. The lowest of Voluntary disclosure index is property and real Estate industry. The resultsalso show that the board of director composition, firm’s size, firm’s operation, and the industrytypes have the significant impact on the level of voluntary disclosure.